Early State Formation in the Maya Lowlands in the Preclassic (1000 BCE - 150 CE) - Dmitri D. Beliaev (RUDN Journal of World History)
The emergence of the state was one of the crucial moments in human history. Ancient Mesoamerica was one of two main areas of the state formation in the New World in pre-Columbian epoch. Archaeological projects in the Maya Lowlands during last decades shed new light on the early stages of the Maya politogenesis in the Preclassic period. Recent trend in the study of Mesoamerican complex polities consists in defining them just as ‘kingdoms’ without specifying whether they were chiefdoms or states. At the same time some scholars suggest that urbanism and statehood could be identified already in the Middle Preclassic (1000-350 BCE). In the present paper basic traits of the evolution of the Preclassic Maya society will be outlined based on different types of data (settlement patterns, economy, social stratification, ritual and ideology). Archaeological data demonstrate that in beginning of the Late Preclassic (350/300 BCE - 200 CE) Maya societies transformed from chiefdoms with three-tiered settlement system, monumental architecture, and incipient urbanization to more complex polities characterized by four-tiered settlement hierarchies, early urban settlements with massive monumental architecture, and complex intensive agriculture. Analysis of the retrospective Maya hieroglyphic inscriptions of the Classic period (200-900 CE) shows that in the Maya historical memory this time was remembered as the period of the foundation of the most ancient dynasties and polities, and the epoch of the establishing of the political order. The beginning of the process of the formation of the Maya early states could be dated between 350 and 200 BCE.